2019
DOI: 10.1016/j.mex.2019.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Carbon-Alumina (C/Al2O3) aerogel nanocomposite for benzene adsorption from flow gas in fixed bed reactor

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The best porous character with highly distributed SDS-alumina spots is obtained at low dopant ratio and autoclave heating conditions (CNT-Al-0.5 autoclave) (Figure A–C). The formation of the mixed aluminum/carbon-based composites was reported by Maity et al and Rastegar et al to combine the advantages of carbon materials and SDS-alumina and improve the adsorption performance. The results obtained in this work confirm the improvement of the adsorption capacity for the removal of arsenic and mercury in the autoclave heating condition (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The best porous character with highly distributed SDS-alumina spots is obtained at low dopant ratio and autoclave heating conditions (CNT-Al-0.5 autoclave) (Figure A–C). The formation of the mixed aluminum/carbon-based composites was reported by Maity et al and Rastegar et al to combine the advantages of carbon materials and SDS-alumina and improve the adsorption performance. The results obtained in this work confirm the improvement of the adsorption capacity for the removal of arsenic and mercury in the autoclave heating condition (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Among these substances, benzene is a carcinogenic compound which is really harmful to human health, and long-period exposure to it has destructive effects on the immune system, the respiratory organs, and the lymph glands [5]. Therefore, emission control and removal of benzene from vapors before releasing to the atmosphere are very important [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in the light of exploring more useful adsorbents, the constructing of carbon aerogel as adsorbent have been extensively investigated owing to their unique properties including high surface area, low density, high selectivity, and easy recovery [10]. In ddition, absorption capacity of these aerogels does not change even after a long period of time and conducting many adsorptions/desorption cycles [6,11], so that previous studies have reported that the absorption capacities of typical carbon aerogels are usually higher than those of granulated active carbon, against the same pollutants [12,13]. In this regard, carbon aerogels are usually prepared by monomers such as resorcinol, formaldehyde and furfuran, in a suitable solvent [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation